2010
DOI: 10.1103/physrevlett.105.026102
|View full text |Cite
|
Sign up to set email alerts
|

Pentagons and Heptagons in the First Water Layer on Pt(111)

Abstract: Scanning tunneling topography of long-unexplained "square root of 37" and "square root of 39" periodic wetting arrangements of water molecules on Pt(111) reveals triangular depressions embedded in a hexagonal H2O-molecule lattice. Remarkably, the hexagons are rotated 30° relative to the "classic bilayer" model of water-metal adsorption. With support from density functional theory energetics and image simulation, we assign the depressions to clusters of flat-lying water molecules. 5- and 7-member rings of H2O m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
246
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(272 citation statements)
references
References 21 publications
22
246
1
3
Order By: Relevance
“…As reported by Kimmel et al (36) and confirmed by our previous STM work (31), water deposited at 135-150 K onto Pt(111) first forms a one-molecule-thin wetting layer (37)(38)(39)(40). Then, isolated 3D ice crystallites emerge and eventually, at thicknesses of ∼3-10 nm, coalesce into a continuous multilayer film.…”
Section: Resultssupporting
confidence: 55%
“…As reported by Kimmel et al (36) and confirmed by our previous STM work (31), water deposited at 135-150 K onto Pt(111) first forms a one-molecule-thin wetting layer (37)(38)(39)(40). Then, isolated 3D ice crystallites emerge and eventually, at thicknesses of ∼3-10 nm, coalesce into a continuous multilayer film.…”
Section: Resultssupporting
confidence: 55%
“…Nie et al's recent examination of water on Pt(111) 13 has provided a new way to think about wetting layer structures. Their STM data showed that the first water layer on Pt(111) has two levels, and that its periodicity reflects an ordered arrangement of patches of low-lying water molecules.…”
mentioning
confidence: 99%
“…A natural way to add them without breaking bonds is to incorporate them in boundaries between clusters of differently rotated hexagons. 13 Replacing four water molecules arranged in a "Y" by a hexagon converts a flat, hexagonally-coordinated mesh of H 2 O into a two-level mesh, with hexagons of flat-lying H 2 O connected by 5-and 7-fold rings of molecules, to chains of dangling-H molecules in hexagons misoriented azimuthally by 30…”
mentioning
confidence: 99%
“…Due to the relative strength and particular directionality of interactions between water molecules, which are delicately balanced against molecule-surface interactions, the structures of water monolayers on various surfaces exhibit surprising diversity. This has been recently demonstrated in scanning tunnelling microscopy (STM) studies [5][6][7][8] , which allow direct visualization of hydrogen bonding networks. The most detailed insight into water adsorption has been achieved for single-crystal metal surfaces, where the structure of water layers is determined mainly by the dimensions of the surface unit cell and the strength of metal-oxygen bonding 6 .…”
mentioning
confidence: 99%